2005
DOI: 10.2174/1567201053586047
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Drug Delivery for Brain Targeting

Abstract: Many drugs are not being effectively and efficiently delivered using conventional drug delivery approach to brain or central nervous system (CNS) due to its complexity. The brain and the central nervous system both have limited accessibility to blood compartment due to a number of barriers. Many advanced and effective approaches to brain delivery of drugs have emerged in recent years. Intranasal drug delivery is one of the focused delivery options for brain targeting, as the brain and nose compartments are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(104 citation statements)
references
References 72 publications
(90 reference statements)
1
101
0
2
Order By: Relevance
“…Recent evidence of direct nose-to-brain transport and direct access to CSF of neuropeptides bypassing the bloodstream has been shown in human trials, despite the inherent difficulties of delivery. 16,17 Intranasal delivery is noninvasive and essentially painless, does not require sterility regulations, and is readily administered by the patient or health professionals. DDS are designed to promote the localized therapeutic effect and minimize toxic side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence of direct nose-to-brain transport and direct access to CSF of neuropeptides bypassing the bloodstream has been shown in human trials, despite the inherent difficulties of delivery. 16,17 Intranasal delivery is noninvasive and essentially painless, does not require sterility regulations, and is readily administered by the patient or health professionals. DDS are designed to promote the localized therapeutic effect and minimize toxic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The mucoadhesive polymeric NPs of TQ that we developed are expected to offer many advantages over conventional nasal dosage forms, such as increased nasal residence and possibility of drug release at a slow and constant rate to the brain. 17,19,20 As part of the development studies for TQ delivery into the brain, the objective of the present study was to simultaneously investigate the plasma pharmacokinetics and brain distribution profiles of the TQ-loaded NPs in Wistar rats after intravenous and intranasal administration and to assess whether there is a direct nose-to-brain transport pathway.…”
Section: Introductionmentioning
confidence: 99%
“…PValue < 0.05 was considered statistically significant. The extent of nose-to-brain delivery could be evaluated by many parameters (Abdelbeary, Tadros, 2013): (i) The brain/blood ratio, at 0.5 h, following intranasal and intravenous administration (Vyas et al, 2005). (ii) The relative bioavailability (RB) percentages following the intranasal administration in the blood and brain (MD et al, 2012).…”
Section: Procedures Of Drug Extraction From Plasma By Liquidliquid Extmentioning
confidence: 99%
“…However, mucocilliary clearance limits the residence time when drug solutions are delivered intranasally. [90]. Recently, Wen et al (2011) demonstrated that intranasal administration showed improved therapeutic efficacy of urocortin (corticotrophin releasing factor related peptide) when encapsulated in Odorranalectin (bioadhesive from lectin family) functionalized PEG-PLGA nanoparticles in hemiparkinsonian rats [91].…”
Section: Routes Of Administration To Enhance Drug Delivery Across Bbbmentioning
confidence: 99%